The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/jcph.566
|View full text |Cite
|
Sign up to set email alerts
|

Ceftolozane/tazobactam pharmacokinetic/pharmacodynamic‐derived dose justification for phase 3 studies in patients with nosocomial pneumonia

Abstract: Ceftolozane/tazobactam is an antipseudomonal antibacterial approved for the treatment of complicated urinary tract infections (cUTIs) and complicated intra‐abdominal infections (cIAIs) and in phase 3 clinical development for treatment of nosocomial pneumonia. A population pharmacokinetic (PK) model with the plasma‐to‐epithelial lining fluid (ELF) kinetics of ceftolozane/tazobactam was used to justify dosing regimens for patients with nosocomial pneumonia in phase 3 studies. Monte Carlo simulations were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 36 publications
5
98
1
1
Order By: Relevance
“…Pending the outcomes of ongoing clinical trials, the results of off-label experiences with P. aeruginosa pneumonia are promising [40]. Nonetheless, in this setting, in the case of TOL/TAZ, the results of studies based on Monte Carlo simulations justify a doubling of the dose approved for cIAIs and cUTIs, also in the light of a plasma-to-epithelial lining fluid ratio of approximately 50% [41]. Other possible indications could be soft tissue and skin infections [42], bloodstream infections [43], and cystic fibrosis exacerbations [44].…”
Section: Perspectivesmentioning
confidence: 99%
“…Pending the outcomes of ongoing clinical trials, the results of off-label experiences with P. aeruginosa pneumonia are promising [40]. Nonetheless, in this setting, in the case of TOL/TAZ, the results of studies based on Monte Carlo simulations justify a doubling of the dose approved for cIAIs and cUTIs, also in the light of a plasma-to-epithelial lining fluid ratio of approximately 50% [41]. Other possible indications could be soft tissue and skin infections [42], bloodstream infections [43], and cystic fibrosis exacerbations [44].…”
Section: Perspectivesmentioning
confidence: 99%
“…70 Spectrum of activity of ceftolozane/ tazobactam includes difficult-to-treat Gram-negative pathogens, including ESBL strains. 28,[71][72][73] Another new therapeutic option is represented by ceftazidime/avibactam, where the new b-lactam inhibitor agent avibactam improves the activity of ceftazidime against MDR P. aeruginosa. 74 Notably, ceftazidime/avibactam has demonstrated consistent activity against KPC-Kp.…”
Section: New Antibioticsmentioning
confidence: 99%
“…In turn, the basis of the work was the 50% plasma-to-ELF penetration ratio of TOL/TAZ. The model clearly demonstrated that, in case of normal renal function, a 3-g dose (each 8 h) of TOL/TAZ is necessary to achieve a >90% probability of target attainment (namely 98%) against PA (as well as Enterobacteriaceae) strains with a minimum inhibitory concentrations (MIC) up to 8 mg/L in ELF [12].…”
Section: Letter To the Editormentioning
confidence: 99%
“…The reason for this double dosage relies on an elegant study where a Monte Carlo simulation was used to assess the kinetics of TOL/TAZ between plasma and the epithelial lining fluid (ELF) [12]. In turn, the basis of the work was the 50% plasma-to-ELF penetration ratio of TOL/TAZ.…”
Section: Letter To the Editormentioning
confidence: 99%